The colonial monetary policy and the exacerbation of the usury phenomenon in Algeria (1830–1898) - remmache, Abdel Fattah; sid ali, Ahmed Masoud (The Algerian Historical Journal, 2026)
An observer of French colonial policy in Algeria realizes that France attempted to create a settler colony based on a capitalist economy that ensured the prosperity of the settlers and served the interests of the mother country, with no consideration for the repercussions on Algerians. In fact, it deliberately impoverished them and shattered social bonds through its legislative machinery. This article aims to highlight the consequences of colonial policy, particularly the imposition and enforcement of French currency in the daily transactions of native Algerians. This had a profound effect on the rise and spread of usury in Algeria during the colonial period, further deepening the misery and destitution that Algerian society endured at the time.